The effect of Src inhibition on ROS triggered signalling in human oesophageal squamous carcinoma cells - Houston-McMillan, Embeth (My University, 2017)
Reactive oxygen species (ROS) have been specifically highlighted as instigators of aberrant pro-survival and proliferative signal transduction pathways in recent years. A possibility that ROS stimulates the Src-Protein Kinase B (PKB)-Glycogen Synthase Kinase (GSK)3-β pathway, a non-canonical pro-survival and anti-apoptotic pathway, was identified and investigated. Specifically, Human Oesophageal Squamous Cell Carcinoma (HOSCC) cells were exposed to oxidative conditions, Src inhibition, and a combination of the two to determine the role that Src plays in the phosphorylation of PKB and GSK3-β in terms of ROS stimulation. Oxidative conditions led to a significant increase in pSrc and pPKB in only one of the 5 HOSCC cell lines being studied; however the abundances of pGSK3-β increased significantly in two of these cells lines and decreased significantly in two of the others. This indicates that oxidative conditions lead to different downstream effects in the various HOSCC cell lines, which are most likely achieved via the activation of various pathways as a result of crosstalk. Src inhibition led to a decrease in pPKB levels across all HOSCC cell lines displaying detectable levels of pPKB, however the abundance of pGSK3-β increased in these cell lines, indicating again that other pathways are at play with respect to the activation of GSK3-β in HOSCC cells. This is due to the fact that GSK3-β is a downstream effector of PKB, and should thus decrease in abundance as pPKB does. Oxidative conditions coupled with Src inhibition resulted in an increase in the abundance of pPKB and pGSK3-β in four of the five HOSCC cell lines. These results indicate that Src inhibition under oxidative conditions may lead to cell survival and proliferation via the activation of pPKB, a pivotal pro-survival protein, and subsequent inactivation of pGSK3-β, a known pro-apoptotic protein. Thus, although more than one pathway is likely to be involved in the phosphorylation of PKB and GSK3-β in HOSCC in terms of ROS, it appears as though inactive Src in HOSCC cells undergoing oxidative stress could be used as a testable marker for HOSCC – a devastating disease affecting numerous South Africans.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2017
Keywords: Esophagus--Cancer; Cell differentiation; Biological response modifiers